2017
DOI: 10.1002/acm2.12222
|View full text |Cite
|
Sign up to set email alerts
|

Normalize the response of EPID in pursuit of linear accelerator dosimetry standardization

Abstract: Normalize the response of electronic portal imaging device (EPID) is the first step toward an EPID‐based standardization of Linear Accelerator (linac) dosimetry quality assurance. In this study, we described an approach to generate two‐dimensional (2D) pixel sensitivity maps (PSM) for EPIDs response normalization utilizing an alternative beam and dark‐field (ABDF) image acquisition technique and large overlapping field irradiations. The automated image acquisition was performed by XML‐controlled machine operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 25 publications
5
37
0
Order By: Relevance
“…Similar to Cai et al. 's 16 work, we found that the PSM was stable at the <1% level for measurements separated by 3 months. Cai reported energy/modality dependence for the PSM, but we found the PSM to be energy/modality independent for photons.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to Cai et al. 's 16 work, we found that the PSM was stable at the <1% level for measurements separated by 3 months. Cai reported energy/modality dependence for the PSM, but we found the PSM to be energy/modality independent for photons.…”
Section: Discussionsupporting
confidence: 91%
“…For fixed radiation fields, we also intercompare field measurements spanning a range of lateral offsets that could be attained by the imager to confirm position independence. This, in effect, cross‐validates our method with those of Greer et al 13 and Cai et al, 16 who inter‐related shifted EPID measurements to derive the PSM. For this series of measurements, the imager was placed at the isocenter plane and the jaws adjusted to produce long‐narrow beams (slits) on the EPID imager.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…Specifically, the work of Yaddanapudi et al 9. provides a method of checking photon beam symmetry using PSM‐corrected EPID images for linac acceptance testing purposes and the work of Bin Cai et al 10. highlights the advantages of PSM‐corrected EPID imaging for beam profile analysis.…”
Section: Introductionmentioning
confidence: 99%
“…One factor is that EPID is mounted on the linac by means of a support arm, and the low-energy scatter ray produced by the interaction between X-rays and the support arm may lead to asymmetry of the EPID image in the inline direction [13,[21][22][23][24][25]; relevant studies show that the effect may exceed 5% [26,27]. The other factor is that EPID requires dark field and flood field calibration to ensure that the response of each pixel is constant, which results in the off-axis response of EPID being different from the actual output of the linac [28,29]. Therefore, when EPID is used as a dosimetry tool, these two factors must be corrected before converting pixel values into dose values.…”
Section: Introductionmentioning
confidence: 99%